Об одном обобщении метода усреднения - Валеев, К.Г.; Джалладова, И.А. (Український математичний журнал, 1997)
Розглянуто випадок, коли можна знайти достатні умови збіжності і аналітичності матричних рядів, які використовуються для побудови системи моментних рівнянь. We consider one case where it is possible to establish sufficient conditions for the convergence and analyticity of matrix series used for the construction of a system of moment equations.